Inducción y utilización de tubérculos in vitro de papa. - Estrada, Rolando; Schilde-Rentschler, Lieselotte; Dodds, John H.; Tovar, Pilar (Federación Colombiana de Cultivadores de Papa, 2018)
Papa-Solanum tuberosum